Essential oils as alternative halal therapeutic source for lung cancer: a mini review - Abdullah, Nazurah; Hazahari, Noor Yuslida; Amid, Azura (IIUM Press, 2022)
The global Muslim population is predicted to grow significantly. The market for Halal products, an obligation for Muslims, is expanding in sync with the Muslim population. Cancer is a notable cause of death globally. Pharmaceuticals are the most important fundamental component because they are disease-specific, most notably cancer-specific. Optional pharmaceuticals were looked into to meet Muslim demand for Halal products. Some essential oils are viable therapeutic sources because they have long been used in conventional medicine for various treatments. The purpose of this study is to review the investigation done on the potential for essential oils to be used as a Halal alternative therapy for lung cancer. This mini review follows the traditional narrative review study. According to these researches, essential oils are helpful in the treatment of malignancies, notably lung cancer. However, additional research, including clinical trials, is essential to enhance the treatment's efficacy.